GOVERNANCE PROCESS IN PT. PUPUK KALIMANTAN TIMUR: A SEARCHING MEANING OF GOOD CORPORATE GOVERNANCE - Evi Malinda (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This research is a case study conducted on a private company in Indonesia which is predicated as a company with the best good corporate governance in 2007, 2008, 2009, 2010, and 2011 respectively. In the number of cases of failure to implement the good corporate governance, on the contrary, PT. Pupuk Kalimantan Timur has shown their successful in implementing their good corporate governance. It certainly attracted the public attention, especially for the author of this research to know directly how the governance process in PT. Pupuk Kalimantan Timur encountered certain excellences and constraints. This research also tries to interpret the meaning of good corporate governance in their governance process to discover the uniqueness of PT. Pupuk Kalimantan Timur which believed as one of success key of PT. Pupuk Kalimantan Timur in implement their good corporate governance. The results of this research shows if PT. Pupuk Kalimantan Timur certainly has almost implemented all good corporate governance principles well, has some excellence and constraints, and also has a uniqueness in translating or interpreting the meaning of good corporate governance. Keyword: governance process, excellences, constraints, the meaning of good corporate governance, uniqueness